Quantification of bioactive compounds in instant coffee and their effects on gastric release using HGT-1 cells - Wan Kamarul Zaman, Wan Syamimi (2020)
Coffee has been found to have been linked with gastrointestinal issues, particularly to the avid coffee drinker. Prepacked instant coffee is a common drink in most Malaysian households but its influence on stomach acid release was insufficiently studied. This study was carried out to determine the gastric release effect of instant coffee and quantifying the putative compounds responsible for gastric release (chlorogenic acid, caffeine, and N-methylpyridinium). Seven types of instant coffee namely regular (REG), low sugar (LS), low fat (LF), white coffee (WC), white coffee low acid (WCA), decaffeinated (DC), and instant black coffee (BC) were used. The quantification utilizes the high-performance liquid chromatography-diode array detector (HPLC-DAD) system. The in vitro study and flow cytometry analysis (BD FASCANTO II) uses argon laser line (500 mW of the 488 nm) to excite the dye and obtained fluorescent bands in calculating the IPX value for gastric release effect. Statistical analysis of One-way ANOVA analysis was used in HPLC quantification and IPX values between different coffee samples. One-sample T-test was performed for the HGT-1 cell viability ≥70% compared with untreated cells. Independent t-test was used for the comparison between omeprazole or histamine with the non-treated control cells for flow cytometry assay calibration. HPLC results showed caffeine content is significantly higher (p>0.05) in BC (60,212 ± 212 μg/ml) and significantly lower (p>0.05) in DC as compared to other instant coffee samples. The order of caffeine content are as follows: BC > LS > WCA > LF > REG > WC > DC. In addition, the chlorogenic acid content was significantly higher (p>0.05) in the BC sample (35,779 ± 3027 μg/ml) as compared to other instant coffee samples. Meanwhile, there is no significant difference (p>0.05) of chlorogenic acid content between the instant coffee other than BC (BC > LS, WCA, LF, REG, WC, DC). As for N-MP content, the result showed BC (565 μg/ml) is significantly higher compared to other instant coffee samples. The amount of N-MP in WC (52 μg/ml) is significantly lowest (p>0.05) when compared with BC, DC, and LS. However, NMP in WC was not significantly different (p>0.05) in comparison to LF (65 μg/ml) and WCA (71 μg/ml). The order of N-MP content are as follows: BC > DC > LS > REG > WCA > LF > WC. The IPX values of gastric release activity of REG (-0.17 ± 0.007) and DC (-0.16 ± 0.005) are not significantly different (p>0.05) from each other. But both are significantly higher (p>0.05) gastric release when compared to other instant coffee samples (Gastric release order: DC, REG > BC, WC > WCA, LF, LS). Pearson correlation data showed no significant correlation (p>0.05) between the quantitative amount of chlorogenic acids, caffeine, and N-MP with the IPX values in each coffee sample. To conclude, the number of putative compounds in coffee has no significant correlation with the gastric release effect produced. Other pre-existing compounds that make up instant coffee warrant further identification and investigation such as pyrogallol and catechol.